2007
DOI: 10.1210/en.2006-1213
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of a Novel Nonpeptide Antagonist of the Human Gonadotropin-Releasing Hormone Receptor, NBI-42902

Abstract: Suppression of the hypothalamic-pituitary-gonadal axis by peptides that act at the GnRH receptor has found widespread use in clinical practice for the management of sex-steroid-dependent diseases (such as prostate cancer and endometriosis) and reproductive disorders. Efforts to develop orally available GnRH receptor antagonists have led to the discovery of a novel, potent nonpeptide antagonist, NBI-42902, that suppresses serum LH concentrations in postmenopausal women after oral administration. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…ESN364 has similar oral efficacy and potency to the small-molecule GnRH antagonist Elagolix (NBI-42902) to lower plasma LH in castrated monkeys (47). However, the relevant clinical concern for GnRH modulators is the adverse event profile in which a potential comparative advantage for NK3R vs GnRH antagonists can be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…ESN364 has similar oral efficacy and potency to the small-molecule GnRH antagonist Elagolix (NBI-42902) to lower plasma LH in castrated monkeys (47). However, the relevant clinical concern for GnRH modulators is the adverse event profile in which a potential comparative advantage for NK3R vs GnRH antagonists can be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies were, therefore, performed in monkeys, where the affinity for the GnRH receptor was only sixfold lower (K i ¼ 3.5 nM). 59,60 Oral administration of 100 mg/kg 41 completely suppressed LH blood levels over 24 hr in castrated male macaques. A final optimization study was performed to improve the manufacturing reproducibility, as 41 showed stereoisomerism due to the 6-methyl group.…”
Section: G Furamide Derivativesmentioning
confidence: 99%
“…49 Nevertheless, the requirement for frequent parenteral administration and the high cost of such agents make them impractical as a MCM. The development of non-peptidic antagonists suitable for oral administration 50 or slow-release implants (histrelin) may reignite interest in testing these substances. 51…”
Section: Combination Of Androgens With Gnrh-analoguesmentioning
confidence: 99%